Boosting teamwork between scrub nurses and neurosurgeons: exploring the value of a role-played hands-on, cadaver-free simulation and systematic review of the literature - de Laurentis, Camilla; Pirillo, David; Di Cristofori, Andrea; Versace, Alessandro; Calloni, Tommaso; Trezza, Andrea; Villa, Valentina; Alberti, Lucia; Baldo, Angelo; Nicolosi, Federico; Carrabba, Giorgio; Giussani, Carlo (Frontiers in Surgery, 2024)
Recently, non-technical skills (NTS) and teamwork in particular have been demonstrated to be essential in many jobs, in business as well as in medical specialties, including plastic, orthopedic, and general surgery. However, NTS and teamwork in neurosurgery have not yet been fully studied.We reviewed the relevant literature and designed a mock surgery to be used as a team-building activity specifically designed for scrub nurses and neurosurgeons.We conducted a systematic review by searching PubMed (Medline) and CINAHL, including relevant articles in English published until July 15 th , 2023.Then, we proposed a pilot study consisting of a single-session, hands-on, and cadaver-free activity, based on role play. Scrub nurses were administered the SPLINTS (Scrub Practitioners' List of Intraoperative Non-Technical Skills) rating form as a self-evaluation at baseline and 20-30 days after the simulation. During the experiment, surgeons and scrub nurses role-played as each other, doing exercises including a simulated glioma resection surgery performed on an advanced model of a cerebral tumor (Tumor Box, UpSurgeOn®) under an Exoscope. At the end, every participant completed an evaluation questionnaire.A limited number of articles is available on the topic. This study reports one of the first neurosurgical teambuilding activities in the literature. Every participant, both scrub nurses and neurosurgeons, positively evaluated the simulation developed on a roleplay. The use of a physical simulator seems an added value, as the tactile feedback given by the model further helps to understand the actual surgical job, more than only observing and assisting. The SPLINTS showed a statistically significant improvement not only in "Communication and Teamwork" (p = 0.048) but also in "Situation Awareness" (p = 0.031).Our study suggests that team-building activities may play a role in improving interprofessional teamwork and other NTS in neurosurgery. ha eliminato: performed a review of 54 ha eliminato: on